13. SURGICAL SITE INFECTION PREVENTION KNOWLEDE AND ASSOCIATED FACTORS AMONG HEATHCARE WORKERS WORKING IN THE SURGICAL DEPARTMENTS OF KIEN GIANG PROVINCIAL GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of surgical site infection prevention knowledge among healthcare workers and the associated factors.Methods: A cross-sectional descriptive study was conducted among 283 healthcare workers from surgical departments of Kien Giang provincial General Hospital.Results: The average knowledge score for surgical site infection prevention among healthcare workers was 57.9%. Knowledge of postoperative surgical site infection prevention had the highest score at 66.7%, followed by preoperative surgical site infection prevention at 53,9%, and the lowest was intraoperative surgical site infection prevention at 52.9% (p < 0.001). Only 22.3% of healthcare workers had good knowledge of surgical site infection prevention. Healthcare workers in the Surgery-Anesthesia Department had significantly better knowledge of surgical site infection prevention than those in other surgical departments (OR = 0.34; p = 0.001).Conclusion: The very low rate of medical staff with good knowledge of surgical site infection prevention shows that Kien Giang provincial General Hospital needs to strengthen training of medical staff on surgical site infection prevention guidelines.
Keywords: Knowledge; prevention; surgical site infection; healthcare workers.